Plan de marketing para la microempresa Right Service de la ciudad de Quevedo - Ruiz Miñio, José Augusto (2011)
The marketing plan provides a clear vision of the final objective to approach the goal. At the same time, it is a detailed explanation of the business position. The research, "Marketing Plan for RIGHT SERVICE in Quevedo city" was developed at the mentioned business, whose owner is Ángela Defaz. It is located in Octava street between Bolívar and Siete Octubre, Quevedo city, Los Ríos Province. The geographical location is of 1° 3´ 18´´ of south latitude and of 79° 25´ 24´´ of west latitude, altitude of 73 msnm. it last 180 days. The objectives for this research are: to develop a marketing plan for Right Service; To determine customers preferences; To analyze the business strengths; to develop marketing strategies. To identify the most sold product, we checked sales for the last three years. In the market research 85% of those who were interviewed preferred the Ricoh copy machine, because it is a guaranteed brand, it has good quality, the price is not high at all (88%). Another cause of its preference is its economic price. Kotler, et to the (2004) "people demand products with benefits that report them the biggest value and the biggest possible satisfaction" There is a competitive market 66% that improves copy machines every year. These short-term results are the reason why a salesperson is very important in the sale process. To be efficient and effective the marketing plan hast to guarantee promotion and immediate participation in the objective market. The marketing plan consists on: analyzing life-time of this kind of business; financial and marking objectives; strategic plan (FODA), Analysis of the five relevant Porter point; marketing strategies with growth approach such as marketing introduction, determining prices. At the same time it is necessary a Mix Marketing based on PRODUCT, PRICE, PLACE, PROMOTION AND PUBLICITY. This proposal also includes a control and evaluation plan, a marketing action plan for the first year and the business annual budget. Based on all the analysis that has been made, the hypothesis is accepted: "competitive business are the reason of low amount of sales."